2023
DOI: 10.3390/rs15092281
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Potential of UAV-Based Hyperspectral Imagery on Pine Wilt Disease Detection: Influence of Spatio-Temporal Scales

Abstract: Pine wilt disease (PWD), caused by pine wood nematode (PWN, Bursaphelenchus xylophilus), poses a serious threat to the coniferous forests in China. This study used unmanned aerial vehicle (UAV)-based hyperspectral imaging conducted at different altitudes to investigate the impact of spatio-temporal scales on PWD detection in an monoculture Masson pine plantation. The influence of spatio-temporal scales on hyperspectral responses of pine trees infected with PWD and detection accuracies were evaluated by Jeffrie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 40 publications
1
2
0
Order By: Relevance
“…The most significant changes in SPAD occur during the regreening stage, and these notable fluctuations in SPAD values likely aid in achieving good model fits. The research results (Tables 5, 6 and 8) demonstrate that the scale of hyperspectral imagery influences the accuracy of the inversion models, with varying accuracies at different scales, aligning with the findings of Pan [60] and Zhu [61] (overall inversion accuracy: ground > UAV). The study indicates that some PLSR models perform slightly worse than RF models, consistent with previous research [62,63].…”
Section: Accuracy Of Chlorophyll Content Modelssupporting
confidence: 69%
“…The most significant changes in SPAD occur during the regreening stage, and these notable fluctuations in SPAD values likely aid in achieving good model fits. The research results (Tables 5, 6 and 8) demonstrate that the scale of hyperspectral imagery influences the accuracy of the inversion models, with varying accuracies at different scales, aligning with the findings of Pan [60] and Zhu [61] (overall inversion accuracy: ground > UAV). The study indicates that some PLSR models perform slightly worse than RF models, consistent with previous research [62,63].…”
Section: Accuracy Of Chlorophyll Content Modelssupporting
confidence: 69%
“…All four indices calculated using EO-1 Hyperion data could effectively monitor the defoliation in spruce-balsam fir forests infected with spruce budworm [14]. The green normalized difference vegetation index (GNDVI) performed better in the detection experiments of Masson pine disease [15]. Run Yu et al [16] concluded that a random forest algorithm incorporating REP could better classify the disease severity in diseased pine.…”
Section: Introductionmentioning
confidence: 99%
“…There have been many studies using multispectral remote sensing techniques for PWD monitoring [9,11,12]. However, the spectral information obtained from multispectral remote sensing is not sufficient for early identification of PWD due to the subtle spectral response between healthy and early infected pine trees [13]. Through imaging or non-imaging spectral technology, hyperspectral remote sensing technology can obtain continuous spectral information of very narrow electromagnetic band features, which compensates for the shortage of multispectral remote sensing.…”
Section: Introductionmentioning
confidence: 99%